Assessment of food consumption pattern in Uttar Pradesh: A dietary diversity study - SANGEETHA, V; SINGH, PREMLATA; MAHRA, G S; SARKAR, SUJIT; VENKATESH, P; SATYAPRIYA, SATYAPRIYA; TOMAR, B S; WASON, MONIKA (The Indian Journal of Agricultural Sciences, 2017)
Nutrition status of people is decided by the dietary habits of people of a region and it has substantial implications for the quality of life of its population. In this background, a study had been undertaken with the objective of understanding dietary habits with special reference to dietary diversity and nutritional status among rural population. The study is based on the primary data collected in Baghpat district of Uttar Pradesh during the year 2014-15. The body mass index, one of the indicator of nutrition status reveals about 10 per cent men, 20 per cent women, 30 per cent boys and 35 per cent girls were coming under underweight and remaining fell in overweight category. Nutrition awareness among the female groups was better than male groups and anganwadi workers were the key informants. The actual consumption of all the food groups were about 50 per cent less than the recommended dietary allowance (RDA) across all the categories. Home produced milk consumption was near to RDA and market depended pulses were more deficient in their consumption. The Individual Diet Diversity Score (IDDS) ranged from 7.6 to 8.0; womens’ dietary diversity score was slightly less than men, similar was the case with children. Simpson Index of Dietary Diversity (SIDD) ranged from 0.69 to 0.77. As evidenced from this study, household production enhances food accessibility, hence, promotion of diversified cropping pattern could be a right strategy for enhancing nutritional security in rural areas. Further, this study suggests to target men as well women for sensitization and awareness programme about importance of food and nutrition to achieve nutritional security of all in particular women.